Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

Boolean Algebra Problem-set Solutions

Madhav P. Desai
January 22, 2024

Show the following (starting from the axioms of a Boolean algebra, using
the results proved in class):

1. The 0 and 1 elements in a Boolean algebra are unique.

• Let u, v be two 0− elements. Then

u = (u + v) = v

Thus the 0−element is unique. If p, q are two 1−elements, then

p = (p.q) = q

and thus the 1−element is unique.

2. a.0 = 0 for each element a. Note that a + 1 = 1 was proved in class.

• a.0 + 0 = a.0 + 1.0 = (a + 1).0 = 1.0 = 0

3. a + 1 = 1 for each element a.

• This was proved in class.

a + 1 = a + (a + a) = (a + a) + a = a + a = 1

4. For each element a, a + a = a, and a.a = a.

• The first one was proved in class. To prove the second:

a.a = a.a + 0 = a.a + a.(¬a) = a.(a + (¬a)) = a.1 = a

1
5. Prove the second De Morgan law:

a.b = a + b

• Confirm that (¬a) + (¬b) is the complement of (a.b).

6. In a finite Boolean algebra with at least two elements, 0 6= 1.

• If 0 = 1, then there is a second element p 6= 0, 1 in the Boolean


algebra. But 1.p = 0.p = 0 which means that p = 0, a contradic-
tion.

7. In a finite Boolean algebra with at least two elements, the set of atoms
is non-empty.

• There is at least one p 6= 0. Thus we can find u ≤ p. If the only


possible u is 0 or p, then p is an atom. Else there is q ≤ p, q 6= 0
and q 6= p. Continue from q. This must terminate when you get
an atom (finiteness).

8. In a finite Boolean algebra with at least two elements, for every x 6= 0


there is at least one atom a ≤ x.

• Finite-ness, same argument as above.

9. If a ≤ b and c ≤ b, then (a + c) ≤ b.

(a + c).b = a.b + c.b = a + c

10. If a ≤ b then b ≤ a.

(¬b).(¬a) = (¬(b + a)) = (¬b).

11. If a ≤ b and a ≤ c, then a ≤ b.c.


a = a.c = a.b.c = a.(bc)

2
12. Prove that a.b + a.b = b.

(¬a).b + (a.b) = ((¬a) + a).b = 1.b = b

13. Prove that


a.b.c + a.b.c + a.b = b
(note: starting from the axioms).

a.(¬b).c + a.(¬b).(¬c) + (¬a).(¬b) =


a.(¬b).(c + (¬c)) + (¬a).(¬b) =
a.(¬b) + (¬a).(¬b) =
(a + (¬a)).b = 1

You might also like